LOW GRADE GLIOMA CLINIC - ESTABLISHING AN INNOVATIVE SERVICE BASED ON A MULTIDISCIPLINARY APPROACH. (3rd October 2018) - Lavrador, José Pedro; Robinson, Charlotte; Hurwitz, Victoria; Giamouriadis, Anastasios; Vergani, Francesco; Ashkan, Keyoumars; Bhangoo, Ranj; Kandeel, Hussein
Abstract: Patients diagnosed with a low grade glioma (LGG) are unique in terms of the uncertainty they experience with the disease, its prognosis and the different treatment approaches. In recognition of these needs, the low-grade glioma clinic aims to provide an individualized approach provided by a specialised multidisciplinary team which includes neuro-surgeons, neuro-psychologist, neurologist, speech therapist and clinical nurse specialist that is able to plan the patient's treatment pathway. The nature of the clinic is to allow for longer consultations tailored to patients' need in recognition of difficult treatment decisions considering the high psychological burden they may have in patients' lives. To maximise time and potentiate the care provided by this specialised team, the clinic is divided into two group of patients: those who require physical assessment or treatment decisions attend in person and those in regular follow-up who do not attend but a proper feedback is provided. This clinic happens once every month. During the first 3 months, 20 patients were considered (10 attendants, 9 virtually reviewed and 1 patient did not attend); 4 patients had a previous histological diagnosis (2 oligodendrogliomas WHO grade II, 1 pilocytic astrocytoma WHO grade I and 1 ganglioglioma WHO grade I) and 16 patients were consider after initial presentation or follow-up of an incidental finding. As the main outcomes of this clinic: 12 patients were listed for surgery, 6 patients for follow-up (repeat imaging – 4 patients, neurology review – 1 patient, oncology review – 1 patient), and 1 was discharged. The EORTC QLQ - BN20 is completed prior to their consultation. We have found that 45% of patients feel 'very uncertain about the future' and 54% were 'quite concerned about disruption to family life'. Overall, these statistics highlight the importance of this clinic in the global therapeutic approach of LGG patients.